Evaluation of anti bacterial activity of punica granatum peels extracts, on growth of gram-positive bacteria isolated from clinical samples - M. Y. Bane; Hassan J. Mohammad; Hamoudi A. Hameed; Siham S. Shaokat (University of Mosul, 2005)
Thirty samples were collected from patients (10-45) years old, suffered from tonsillitis,pharyngitis, infected wounds, acne & Bronchitis. Gram –positive bacteria were isolated from these samples, and diagnosed, of which, Staphylococcus aureus ( 50%) and Staphylococcus epidermidis (16.66%), Streptococcus pyogenes (13.34%), Streptococcus pneumoniae (10%) and Micrococcus spp (10%). Alcoholic and water extracts of the punica granatum(Pomegranate) peels as well as the dried powders were prepared, the effect of these extracts were studied against these isolates. The antimicrobial susceptibility tests of the extracts were determined by Kirby- Bauer method and the MICs were determined. The antibacterial activity of punica granatum(Pomegranate) peels was determined. The alcoholic extract showed more potent inhibitory effect on the isolates than water extract, and the best effect was on the growth of Staphylococcus epidermidis followed by Staphylococcus aureus , Micrococcus spp, Streptococcus pyogenes and Streptococcus pneumoniae. The zone of inhibition was (17- 23mm) for alcoholic extract and( 12-23mm) for watery extract. The antibacterial activity of pomegranate peels extracts should make it useful for treatment of wounds, skin infections, tonsillitis and pharyngitis caused by the above bacteria.